Developing a Pesantren-Based Soft Skill Education Management Model for Vocational School in the Ma'arif Education Institute, Semarang Regency - Hanik, Ahmad; Rachman, Maman; Samsudi, Samsudi; Ekosiswoyo, Rasdi (Universitas Negeri Semarang, 2019)
This research focuses on the development of pesantren-based soft skill education management model in vocational school. The researchers have reviewed curriculum changes, ranging from the active-student learning curriculum (CBSA), competence-based curriculum (KBK), school-based curiculum or Education Unit Level Curriculum (KTSP) to 2013 Curriculum (K13), and changes in the education management paradigm starting from the concept of teachin-learning strategies, soft skill management, to Community Based Education Management. In Permendiknas Number 23 of 2006 concerning Graduates' Competency Standards for Primary and Secondary Education Units, soft skill gets a more dominant portion than hard skill. Conceptually, the indicators in Permendiknas Number 23 Year 2006 should be sufficient for SMK students to be fully aware of the formation of a noble person. However, in reality there are still many gaps regarding the achievement of the Graduates Competency Standards (SKL). Thus, reconstruction is needed in the learning process in Vocational Schools especially in the achievement of these soft skills. Therefore, managerial approaches are needed; one of which is the pesantren-based soft skills education management model. It is a model with a noble moral development approach for students who live in boarding schools. The learning and guidance model in Islamic boarding school (Pesantren) is applied in vocational schools without leaving the culture of the Islamic boarding school.